2020
DOI: 10.1136/bmjopen-2020-036925
|View full text |Cite
|
Sign up to set email alerts
|

Death and dying in prehospital care: what are the experiences and issues for prehospital practitioners, families and bystanders? A scoping review

Abstract: ObjectiveTo identify the factors that shape and characterise experiences of prehospital practitioners (PHPs), families and bystanders in the context of death and dying outside of the hospital environment where PHPs respond.DesignA scoping review using Arksey and O’Malley’s five-stage framework. Papers were analysed using thematic analysis.Data sourcesMEDLINE; Embase; CINAHL; Scopus; Social Sciences Citation Index (Web of Science), ProQuest Dissertations & Theses A&I (Proquest), Health Technology Assess… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 78 publications
(108 reference statements)
0
16
0
Order By: Relevance
“…However, little is known about patient and family caregiver experiences of end-of-life emergency ambulance care. 4,5 A need for more research into the role of paramedics as generalist palliative care providers has been identified. 2,[5][6][7] People in developed countries are living longer, with more complex chronic illnesses and a desire to live and die in their own homes.…”
Section: Introductionmentioning
confidence: 99%
“…However, little is known about patient and family caregiver experiences of end-of-life emergency ambulance care. 4,5 A need for more research into the role of paramedics as generalist palliative care providers has been identified. 2,[5][6][7] People in developed countries are living longer, with more complex chronic illnesses and a desire to live and die in their own homes.…”
Section: Introductionmentioning
confidence: 99%
“…Several protocols have been developed to support health professionals in the communication of bad news, but none have answered the needs revealed by the families of sudden death victims [1,14], which require orientations on how to give bad news when there are several people present [15] and present the news in a chaotic and violent environment as it happens in the prehospital environment [1,16].…”
Section: Introductionmentioning
confidence: 99%
“…Concurrently, paramedics are increasingly subjected to threats from patients or bystanders, with a majority of EMS personnel, between 57 to 93%, having reportedly encountered physical and verbal abuse in their work during the last decade [ 5 , 6 ]. The continuous imbalance of high-intensity and psychologically demanding assignments with more mundane, low-acuity experiences can affect paramedics’ professional quality of life [ 7 , 8 ] as they often feel emotionally affected by patient encounters, which manifests in symptoms of traumatic stress [ 9 , 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…Stressors increasing the risk of secondary trauma, both STS and BO, derive from feelings of hopelessness, associated commonly with paramedics’ assignment experiences involving, among others, death and drug overdoses [ 9 , 16 ], as well as a sense of powerlessness in helping others in need, prevalent in cases of social distress [ 10 , 17 ]. In addition, paramedics’ repeated non-acute encounters might cause professional role dissonance, in comparison to the more historical profile of paramedics as critical life-savers [ 7 ], with potential implications on paramedics’ compassion satisfaction (CS).…”
Section: Introductionmentioning
confidence: 99%